Retraction notice to "Stability and global Hopf bifurcation in a delayed predator–prey system" [Nonlinear Analysis RWA 11(2) (2010) 959–977]. (June 2019) - Yuan, Sanling; Zhang, Fengqin
Abstract: This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editors-in-Chief. This article is highly similar to S. Yuan and Y. Song "Bifurcation and stability analysis for a delayed Leslie-Gower predator–prey system", IMA J. Appl. Math. 74 (4) (2009), 574–603 [ http://dx.doi.org/10.1093/imamat/hxp013 ]. Our policy states that "Submission of an article implies that the work described has not been published previously (except in the form of an abstract or as part of a published lecture or academic thesis or as an electronic preprint, see http://www.elsevier.com/postingpolicy ), that it is not under consideration for publication elsewhere, that its publication is approved by all authors and tacitly or explicitly by the responsible authorities where the work was carried out, and that, if accepted, it will not be published elsewhere in the same form, in English or in any other language, including electronically without the written consent of the copyright-holder". As such this article represents a violation of the journal's publishing policies.